THE RELATIONSHIP OF SCOUT EXTRACURRICULAR ON THE STUDENTS’ DISCIPLINE - Nureva, Nureva; Tohir, Ahmad (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2020)
This study aims to determine the relationship between scout extracurricular activities on student discipline. This research is a quantitative descriptive. The population in this study were all students who joined the Scout extracurricular at SDN 2 Way Huwi, namely 24 students. The research sample was taken using a purposive sampling technique so that a sample of 10 students was obtained. Data collection techniques are observation, interviews, and questionnaires. Data analysis techniques used the correlation Pearson product-moment with the help of the SPSS program. Based on the results of research and discussion, it can be concluded that there is a positive and significant relationship between scout extracurricular activities and student discipline in SDN 2 Way Huwi with a significance value (0,000 <0.05). Discipline does not only come from parents, teachers, or students themselves, but student discipline can also be trained through scout extracurricular activities.